Sistem Mass Rapid Transit (MRT) DKI Jakarta: Studi Kasus Transfer Kebijakan Pendapatan Non-Farebox di Indonesia - Halifa Nurnadhifa; Hafizhah Nur Latifah (Universitas Warmadewa, 2021)
Policy transfer is the process of borrowing policies from other countries that have successfully implemented the idea in their home country. There are at least four things that need to be known in policy transfer, namely the form, the learning process, the obstacles in it, and errors in policy transfer. This paper will further examine the transfer of the Jakarta MRT policy in terms of the three aspects and see how far the policy transfer has been implemented. With descriptive qualitative research methods, the results of the study show that the transfer of the Jakarta MRT policy itself has been carried out well, although there are still some obstacles and errors in the policy learning process. For this reason, several corrections must be made to make the policy develop.